2007
DOI: 10.1080/15216540701313788
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of glucose transporter type 4 isoform gene expression in muscle and adipocytes

Abstract: SummaryThe gene expression of glucose transporter type 4 isoform (GLUT4) is known to be controlled by metabolic, nutritional, or hormonal status. Understanding the molecular mechanisms governing GLUT4 gene expression is critical, because glucose disposal in the body depends on the activities of GLUT4 in the muscle and adipocytes. The GLUT4 activities are regulated by a variety of mechanisms. One of them is transcriptional regulation. GLUT4 gene expression is regulated by a variety of transcriptional factors in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0
7

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(78 citation statements)
references
References 112 publications
1
69
0
7
Order By: Relevance
“…As expected, the altered expression of critical elements of insulin-stimulated glucose uptake (GLUT4) and of lipogenic pathway (FASN) might be related to altered expression of transcriptional factors, such as SREBF1 (Griffin andSul, 2004 andIm et al, 2007). Here we show that SREBF1 expression in SAT is reduced simultaneously with the expression of both by the isolation procedure.…”
mentioning
confidence: 51%
“…As expected, the altered expression of critical elements of insulin-stimulated glucose uptake (GLUT4) and of lipogenic pathway (FASN) might be related to altered expression of transcriptional factors, such as SREBF1 (Griffin andSul, 2004 andIm et al, 2007). Here we show that SREBF1 expression in SAT is reduced simultaneously with the expression of both by the isolation procedure.…”
mentioning
confidence: 51%
“…TNF correlates with the hyperinsulinemic state and the blockade of TNF production by anti-TNF drugs like infliximab inhibits the development of insulin resistance. Thus, TNF promotes hyperinsulinemia and hyperglycaemia and has been linked to an increased risk of diabetes development [41] . Moreover, non-structural proteins such as NS3 and NS5 interact with the ER.…”
Section: Insulin Resistance In Hepatitis Cmentioning
confidence: 99%
“…However, the attenuated glucose uptake by compound C co-incubation with danthron revealed that danthron exerted such effects mainly through the activation of AMPK in the process. Under this condition, the increased Glut4 translocation by AMPK activation promoted the uptake of extracellular glucose in C2C12 cells [8,32] . However, further studies are needed to elucidate whether the AMPK-induced Glut2-dependent glucose uptake existed and contributed to the lowered glucose content in HepG2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, activated AMPK regulates cholesterol synthesis by phosphorylating and inactivating 3-hydroxy-3-methylglutaryl-CoA reductase [4] . In addition, in adipose and skeletal muscle tissues, AMPK promotes the translocation of glucose transporter type 4 (Glut4) to the cellular membrane to transport glucose [8] . In the liver, AMPK helps regulate glucose homeostasis by reducing the gluconeogenic key genes including phosphoenolpyruvate carboxykinase (PEPCK) and glucose 6-phosphatase (G6Pase) [9,10] .…”
Section: Introductionmentioning
confidence: 99%